Composite binder for super iron ore concentrate pellets and preparation and use methods thereof

By using a composite binder of modified carboxymethyl cellulose (CMC-TAPOB) and organic macromolecular reinforcing agents, the problems of impurities introduced by bentonite and easy cracking of super iron concentrate were solved, and high-quality pellets were prepared.

CN120818684AActive Publication Date: 2025-10-21ANSTEEL GROUP MINING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511319277.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-10-21
Estimated Expiration
2045-09-16

AI Technical Summary

Technical Problem

Existing technologies using bentonite as a binder introduce harmful impurities, affecting blast furnace smelting. Furthermore, super iron concentrate pellets are prone to cracking and have insufficient compressive strength, making it difficult to meet the requirements for high-quality pellets.

Method used

A composite binder using modified carboxymethyl cellulose (CMC-TAPOB) as a binder, organic macromolecular reinforcing agents, and alkaline calcium-containing substances as additives reduces the introduction of silicon and aluminum components, enhances the bonding force between particles, and improves pellet quality.

Benefits of technology

It significantly improves the green pellet quality and compressive strength of super iron concentrate pellets, reduces the tendency to crack, and meets the requirements of blast furnace smelting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention aims to solve the problems existing in the super iron ore concentrate pellet additive technology, and provides a composite binder for super iron ore concentrate pellets and a preparation and use method thereof. The composite binder is prepared from the following components in percentage by mass: 20 to 40 weight percent of binder, 10 to 20 weight percent of reinforcing agent and 40 to 70 weight percent of additive. The modified carboxymethyl cellulose CMC-TAPOB is used as a binder, organic macromolecules are used as a reinforcing agent, an alkaline calcium-containing substance is used as an additive, bentonite is not added, introduction of silicon and aluminum components is reduced, and meanwhile the quality of the super iron ore concentrate pellets is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steel metallurgy pellet production, and in particular relates to a composite binder suitable for preparing pellets from super iron concentrate. Background Art

[0002] Iron ore pellets have excellent metallurgical properties and can improve the permeability of blast furnace charge columns. They are considered to be high-quality charge materials necessary for optimizing blast furnace charge structure. Their role in the steel industry is becoming increasingly important, and their usage is increasing. Therefore, in recent years, major steel companies in my country have been focusing on promoting the development of pellets.

[0003] When producing pellets from iron ore concentrate, a small amount of binder must be added to improve green ball formation, enhance pellet quality, and meet production requirements. This ensures the pellets have a certain strength to maintain integrity during transportation, drying, and roasting, and to meet the requirements of blast furnace smelting. Domestic pelletizing plants mostly use bentonite as a binder. Because bentonite is an aluminosilicate mineral with montmorillonite as its primary component, its inherent composition and properties can introduce harmful impurities and reduce the pellet grade.

[0004] Super iron concentrate is a promising new material, serving as a key raw material for powder metallurgy, magnetic materials, ultrapure iron, and clean steel base materials. Super iron concentrate can also be used as a pelletizing feedstock to produce high-quality pellets. However, since it is a re-selected product of ordinary iron concentrate, it has a higher iron content (≥70%), a lower SiO2 content, and a finer particle size, making it more susceptible to green ball cracking and substandard compressive strength in finished balls.

[0005] The Chinese patent application, "Composite Binder for Improving the Pellet-Forming Performance of Super Iron Concentrate Powder and Its Use Method," with publication number CN 112553460 B, provides a composite binder composed of sodium bentonite, coarse-grained coal powder, a highly absorbent resin, and sodium carboxymethyl cellulose to improve the cracking problem of pellets produced from superfine ore powder and enhance pellet quality. However, it still uses sodium bentonite as the main component, and introduces silicon, aluminum, and other components into the pellets, which has a certain impact on blast furnace smelting. Using super iron concentrate to produce high-quality pellets requires the development of a highly efficient new composite binder that can completely replace bentonite. This can reduce the introduction of various unnecessary impurities into the metallurgical process while ensuring pellet quality, which is of great significance for improving blast furnace quality, reducing consumption, and reducing energy consumption and emissions. Summary of the Invention

[0006] The present invention addresses existing issues in additive technology for super iron ore concentrate pellets and provides a composite binder for super iron ore concentrate pellets, as well as methods for its preparation and use. The composite binder utilizes modified carboxymethyl cellulose (CMC-TAPOB) as a binder, organic macromolecules as a reinforcing agent, and alkaline calcium-containing substances as additives, without the addition of bentonite. This reduces the introduction of silicon and aluminum components and improves the quality of super iron ore concentrate pellets.

[0007] One of the technical solutions of the present invention is a composite binder for super iron ore concentrate pellets, which is composed of the following components in percentage by mass:

[0008] Binder 20-40 wt%

[0009] Reinforcement 10-20 wt%

[0010] Additives 40-70 wt%

[0011] Wherein, the binder is N-(1,3,5-tris(4-aminophenoxy)phenyl)carboxymethyl cellulose (CMC-TAPOB);

[0012] The enhancer is one or more of modified starch, puffed starch, and gelatinized starch;

[0013] The additive is one or more of limestone, quicklime and slaked lime.

[0014] Furthermore, the synthesis method of the composite binder for super iron ore concentrate pellets, the CMC-TAPOB, is as follows:

[0015] (1) Dissolve CMC in phosphate buffer solution with a concentration of 1% to 2.5%; the feed ratio of CMC to phosphate buffer solution is 1:40 to 60 g / mL;

[0016] (2) Add the phosphate buffer solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) dropwise to the CMC phosphate buffer solution and stir at room temperature for 20-40 minutes; wherein the molar ratio of each raw material is: CMC:EDC = 1:2.4-3.0; EDC:NHS = 1:5-10;

[0017] (3) 1,3,5-tris(4-aminophenoxy)benzene TAPOB is completely dissolved in N,N-dimethylformamide (DMF) to form a TAPOB solution, which is then added dropwise to the reaction solution of step (2). The molar ratio of TAPOB to CMC is 1 to 5:1.

[0018] (4) After the reaction is carried out at room temperature in the dark under continuous nitrogen and stirring for 12-24 hours, the reaction mixture is poured into anhydrous ethanol and allowed to stand until no precipitate is formed. The product CMC-TAPOB is obtained by filtration and drying.

[0019] The second technical solution of the present invention is a method for preparing the composite adhesive, wherein the adhesive, reinforcing agent and additive are mixed in proportion at room temperature to obtain a finished product;

[0020] Wherein, the particle size specification of the reinforcing agent is -325 mesh content ≥90%; the particle size specification of the additive is -200 mesh content ≥90%.

[0021] The third technical solution of the present invention is a method for using the above-mentioned composite binder, which is to mix the composite binder and super iron concentrate to form balls, and the amount of the composite binder added is 0.5%-1% of the total amount of the composite binder and the super iron concentrate.

[0022] Furthermore, the method of using the above-mentioned composite binder is as follows: 0.5-1% of the composite binder is added to 99.0-99.5% of super iron concentrate with a water content of 8-9%, and the mixture is vigorously mixed and stirred for 10-15 minutes at room temperature to uniformly disperse the composite binder in the mixture, and then allowed to stand for a certain period of time; the mixture after standing is then pelletized, and the pelletizing time is 9-10 minutes; the subsequent green ball drying, preheating and roasting processes are conventional methods.

[0023] Compared with the prior art, the advantages of the present invention are:

[0024] By adopting the composite binder provided by the present invention, the quality of the prepared pellets is significantly improved, and the reduction expansion rate is also improved.

[0025] Among them, the binder selected by the present invention is modified carboxymethyl cellulose CMC-TAPOB. Due to the modification of TAPOB, the molecular structure of carboxymethyl cellulose is changed, so that CMC-TAPOB has a larger volume and complex structure, and TAPOB belongs to a polyamino group organic compound, which allows CMC to introduce polar groups such as amino groups, which is conducive to CMC-TAPOB combining with the surface active sites of super iron ore powder through polar groups through van der Waals forces, coordination effects, etc., to form a polymer adsorption layer on the surface of super iron ore powder particles. The polymer chains in this adsorption layer can bridge the different iron ore powder particles, connecting the originally relatively independent iron ore powder particles together, thereby increasing the viscosity between the particles, and the bonding advantage is more obvious. In addition, entanglement occurs between the CMC-TAPOB molecular chains, and the intermolecular binding force is further enhanced by interactions such as hydrogen bonds. This effect increases the mutual restraint between the iron ore particles, which is manifested as an increase in the viscosity between the iron ore molecules on a macro scale. In addition, CMC-TAPOB can bind water molecules inside the pellets, preventing water from localized accumulation inside the pellets and reducing the difference in moisture content inside and outside the pellets caused by uneven water migration during the drying process, thereby reducing the tendency to burst.

[0026] The main structure of the reinforcing agent used is an organic macromolecule with a large number of organic functional groups such as carboxyl and hydroxyl groups. When the reinforcing agent is added to make pellets, it can work synergistically with the binder to make the bonding between the iron ore concentrate particles tighter, improve the plasticity of the green balls, enhance the compressive strength of the green balls, and make the pellets stronger.

[0027] After calcining, the additive's primary component is CaO. During the calcination phase, CaO participates in the reaction. Although CaO has a greater affinity for SiO₂ than Fe₂O₃, due to kinetics, the calcium ferrite system is preferentially formed at lower temperatures. The compounds in this system have a low melting point, between 1200°C and 1230°C, and a liquid phase forms at the calcination temperature. This liquid phase wets the surface of the pellets, tightening and rearranging them, making the pellet structure denser. It also dissolves solid particles, promoting recrystallization and crystal growth, and enhancing the strength of the finished pellets. During the calcium ferrite reduction process, a metallic iron layer forms on the surface of the calcium ferrite. This metallic iron forms concentric layers around the ferrite particles, inhibiting pellet expansion and reducing pulverization. DETAILED DESCRIPTION

[0028] A composite binder for super iron ore concentrate pellets, comprising the following components by mass percentage:

[0029] Binder 20-40 wt%

[0030] Reinforcement 10-20 wt%

[0031] Additives 40-70 wt%

[0032] Wherein, the binder is N-(1,3,5-tris(4-aminophenoxy)phenyl)carboxymethyl cellulose (CMC-TAPOB);

[0033] The enhancer is one or more of modified starch, puffed starch, and gelatinized starch, with a -325 mesh content of ≥90%;

[0034] The additive is one or more of limestone, quicklime and slaked lime, and the content of -200 mesh is ≥90%.

[0035] The preparation method of the composite adhesive comprises mixing the adhesive, reinforcing agent and additive in proportion at room temperature to obtain the finished product.

[0036] The method for using the above-mentioned composite binder is to mix the composite binder and super iron concentrate to form balls, and the amount of composite binder added is 0.5%-1% of the total amount of the composite binder and super iron concentrate; that is, 0.5-1% of the composite binder is added to 99.0-99.5% of the super iron concentrate with a water content of about 8~9%, and vigorously mix and stir for 10~15 minutes at room temperature to uniformly disperse the composite binder in the mixture. After mixing evenly, let it stand for a certain time; make balls with the mixture after standing, and the ball making time is 9~10 minutes; the subsequent green ball drying, preheating and roasting processes are conventional methods.

[0037] The synthesis method of the binder CMC-TAPOB in the following examples is:

[0038] (1) CMC was dissolved in phosphate buffer solution with a concentration of 2.0%; the feed ratio of CMC to phosphate buffer solution was 1:50 g / mL;

[0039] (2) A phosphate buffer solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) was added dropwise to a CMC phosphate buffer solution and stirred at room temperature for 30 minutes; wherein the molar ratio of each raw material was: CMC:EDC = 1:2.5; EDC:NHS = 1:7.5;

[0040] (3) 1,3,5-tris(4-aminophenoxy)benzene TAPOB was completely dissolved in N,N-dimethylformamide (DMF) to form a TAPOB solution, which was then added dropwise to the reaction solution of step (2). The molar ratio of TAPOB to CMC was 3:1.

[0041] (4) After the reaction was carried out at room temperature in the dark under continuous nitrogen and stirring for 18 hours, the reaction mixture was poured into anhydrous ethanol until no precipitate was formed. The product CMC-TAPOB was obtained by filtration and drying.

[0042] In the following examples and comparative examples, the prepared green balls are tested for drop strength, green ball compressive strength, and burst temperature. If all indicators of the green balls meet the standard requirements, roasting tests are performed to explore whether the compressive strength and reduction expansion rate of the finished balls meet the standards.

[0043] 1. Comparative Example Experimental Results. Specific experimental results are shown in Table 1.

[0044] Comparative Example 1: Only super iron concentrate was used to make pellets.

[0045] Comparative Example 2: Only carboxymethyl cellulose was used for pelletizing, and the added amount of hydroxymethyl cellulose:super iron concentrate was 0.5%:99.5%.

[0046] Comparative Example 3: Only binder was used for pelletizing, and the addition amount of CMC-TAPOB:super iron concentrate was 0.5%:99.5%.

[0047] Comparative Example 4: Only the reinforcing agent was used for pelletizing, and the added amount of puffed starch:super iron concentrate was 0.5%:99.5%.

[0048] Comparative Example 5: Only additives were used for pelletizing, with the addition amount of limestone:super iron ore being 0.5%:99.5%.

[0049] Comparative Example 6: The composite additive consists of 70% of a binder CMC-TAPOB and 30% of a reinforcing agent puffed starch in percentage by mass, and the added amounts of the composite additive and the super iron concentrate are 0.5% and 99.5%.

[0050] Comparative Example 7: The composite additive consists of 30% of binder CMC-TAPOB and 70% of additive limestone in percentage by mass, and the addition amount of composite additive: super iron concentrate is 0.5%:99.5%.

[0051] Comparative Example 8: The composite additive consists of 20% of the enhancer puffed starch and 80% of the additive limestone in percentage by mass, and the added amounts of the composite additive and the super iron concentrate are 0.5%:99.5%.

[0052] Comparative Example 9: The composite additive is composed of 30% of binder CMC, 15% of reinforcing agent puffed starch, and 55% of additive limestone in percentage by mass, and the added amount of composite additive: super iron concentrate is 0.5%:99.5%.

[0053] Table 1. Performance of raw and finished balls of comparative examples 1 to 9

[0054]

[0055] It can be seen from Table 1 that when super iron concentrate, binder, reinforcing agent and additive are used alone to make balls, the green ball indicators are all unqualified; when a composite binder of a binder and additive or a composite binder of an additive and reinforcing agent is used, the green ball indicators are unqualified; when a composite binder of a binder and reinforcing agent is used, the green ball indicators meet the standards, but after roasting, the compressive strength and reduction expansion rate of the finished balls do not meet the requirements.

[0056] 2. Experimental results of the embodiment: see Table 2 for data.

[0057] The mass percentages of the components of the composite binder of Example 1 are 20% binder, 10% reinforcing agent, and 70% additive. The addition amounts of composite binder: super iron concentrate are 0.5%: 99.5%;

[0058] The mass percentages of the components of the composite binder of Example 2 are 25% binder, 12% reinforcing agent, and 63% additives. The addition amounts of composite binder: super iron concentrate are 0.5%: 99.5%;

[0059] The mass percentages of the components of the composite binder of Example 3 are 30% binder, 15% reinforcing agent, and 55% additive. The addition amounts of composite binder: super iron concentrate are 0.5%: 99.5%;

[0060] The mass percentage of each component of the composite binder of Example 4 is 35% binder, 18% reinforcing agent, 47% additive, and the addition amount of composite binder: super iron concentrate is 0.5%: 99.5%;

[0061] The mass percentage of each component of the composite binder of Example 5 is 40% binder, 20% reinforcing agent, and 40% additive. The addition amount of composite binder: super iron concentrate is 0.5%: 99.5%;

[0062] The mass percentage of each component of the composite binder of Example 6 is 30% binder, 15% reinforcing agent, 55% additive, and the addition amount of composite binder: super iron concentrate is 0.75%: 99.25%;

[0063] The mass percentages of the components of the composite binder of Example 7 are 30% binder, 15% reinforcing agent, and 55% additives, and the addition amounts of composite binder:super iron concentrate are 1.0%:99.0%.

[0064] Among them, the enhancer is gelatinized starch, with a -325 mesh content of ≥90%; the additive is slaked lime, with a -200 mesh content of ≥90%.

[0065] The preparation method of the composite adhesive comprises mixing the adhesive, reinforcing agent and additive in proportion at room temperature to obtain the finished product.

[0066] The method of using the above-mentioned composite binder is to weigh the composite binder and super iron concentrate according to the proportions of the above-mentioned embodiments. The water content of the super iron concentrate in the above-mentioned embodiment is 8.64%. Mix and stir vigorously at room temperature for 12 minutes to evenly disperse the composite binder in the mixture. After mixing evenly, let it stand for a certain period of time, and then make balls with the mixture after standing for 9 minutes. The subsequent drying, preheating and roasting processes of the raw balls are conventional methods.

[0067] Table 2. Performance of raw and finished balls of Examples 1 to 7

[0068]

[0069] From the data, it can be seen that when the composite binder prepared by the present invention is used in production, the average drop strength of the green ball is ≥4.5 times·0.5 m -1 , the average compressive strength of the green balls is ≥11.0N. During the ball making process, it was found that after adding the organic binder, the surface of the green balls became smooth and the burr phenomenon was significantly reduced. The formula of the composite binder of the present invention was selected to avoid the bursting of the pellets during the heating process. When the amount of binder component in the composite binder increased, the average drop strength of the green balls was significantly improved, which shows that CMC-TAPOB has a certain positive effect on the drop strength of the green balls; with the increase in the amount of reinforcing agent, the compressive strength of the green balls was significantly improved; with the increase in the amount of additives, the compressive strength of the finished balls increased and the reduction expansion rate decreased. The composite binder of the present invention can be used to prepare high-quality super iron ore pellets that meet the standard requirements.

[0070] Example 8

[0071] A composite binder for super iron concentrate pellets, comprising the following components in percentage by mass: 20% binder, 10% modified starch, and 70% limestone; and the addition ratio is 0.75% composite binder: 99.25% super iron concentrate.

[0072] The preparation method of the composite adhesive in this embodiment is the same as that in Example 1.

[0073] The method of using the composite binder in this embodiment is the same as that in Example 1, except that the water content of the super iron concentrate is 8.87%, the mixing time is 10 minutes, and the pelletizing time is 10 minutes.

[0074] Example 9

[0075] A composite binder for super iron concentrate pellets, comprising the following components in percentage by mass: 20% binder, 5% puffed starch, 5% modified starch, 10% limestone, and 60% quicklime; the addition amount is 0.75% composite binder: 99.25% super iron concentrate.

[0076] The preparation method of the composite adhesive in this embodiment is the same as that in Example 1.

[0077] The method of using the composite binder in this embodiment is the same as that in Example 1, except that the water content of the super iron concentrate is 8.12%, the mixing time is 15 minutes, and the pelletizing time is 9 minutes.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A composite binder for super iron ore concentrate pellets, characterized in that: It is composed of the following components by mass percentage: Binder 20-40 wt% Reinforcement 10-20 wt% Additives 40-70 wt% Wherein, the binder is N-(1,3,5-tris(4-aminophenoxy)phenyl)carboxymethyl cellulose, namely CMC-TAPOB; The enhancer is one or more of modified starch, puffed starch, and gelatinized starch; The additive is one or more of limestone, quicklime and slaked lime.

2. The composite binder for super iron ore concentrate pellets according to claim 1, characterized in that: The synthesis method of the CMC-TAPOB is: (1) Dissolve CMC in phosphate buffer solution with a concentration of 1% to 2.5%; the feed ratio of CMC to phosphate buffer solution is 1:40 to 60 g / mL; (2) Add the phosphate buffer solution containing EDC and NHS dropwise to the CMC phosphate buffer solution and stir at room temperature for 20-40 minutes; wherein the molar ratio of each raw material is: CMC:EDC = 1:2.4-3.0; EDC:NHS = 1:5-10; (3) TAPOB was completely dissolved in DMF to form a TAPOB solution, which was then added dropwise to the reaction solution of step (2), with the molar ratio of TAPOB to CMC being 1 to 5:1; (4) After the reaction is carried out at room temperature in the dark under continuous nitrogen and stirring for 12-24 hours, the reaction mixture is poured into anhydrous ethanol and allowed to stand until no precipitate is formed. The product CMC-TAPOB is obtained by filtration and drying.

3. The method for preparing the composite adhesive according to claim 1, characterized in that: The finished product is obtained by mixing the binder, reinforcing agent and additives in proportion at room temperature; Wherein, the particle size specification of the reinforcing agent is -325 mesh content ≥90%; The particle size specification of the additive is -200 mesh content ≥90%.

4. The method for using the composite adhesive according to claim 1, characterized in that: The composite binder and the super iron concentrate are mixed to form balls, and the amount of the composite binder added is 0.5%-1% of the total amount of the composite binder and the super iron concentrate.

5. The method for using the composite adhesive according to claim 4, characterized in that: 0.5-1% of the composite binder is added to 99.0-99.5% of the super iron concentrate with a moisture content of 8-9%, and the mixture is vigorously mixed and stirred at room temperature for 10-15 minutes to uniformly disperse the composite binder in the mixture, and then allowed to stand for a certain period of time; the mixture after standing is then pelletized for 9-10 minutes; the subsequent green ball drying, preheating and roasting processes are conventional methods.

Citation Information

Patent Citations

  • Composite binder for improving the pelletizing properties of super iron concentrate powder and its application method

    CN112553460B

  • Organic binder and method for preparing pellet material for fluidizing chlorination furnace

    CN111302392A

  • Iron-rich low-silicon composite binder for iron ore pellets and preparation method of iron-rich low-silicon composite binder

    CN120026177A

  • Method for pelletizing raw material for iron making

    JP2004076134A

  • Modified native starch base binder for pelletizing mineral material

    US5306327A